READING TASK QUALITY IN LEARNING TEXTBOOK: COGNITIVE AND RELIGIOUS PERSPECTIVE - Nisrina, Nisrina (Universitas Muhammadiyah Makassar, 2024)
This study explored the allocated HOTs, MOTs, and LOTs in tasks that should be accomplished. Another issue was the religious task inserted in the learning textbook. The primary data in this study was English textbooks taught in Indonesia. The study used Bloom's classification of students' cognitive level. As for the religious aspect, hadith transmitted by Muslim was used as the indicator, those are Faith, Moral, and Sharia. A coding scheme was accordingly developed to ease in digging the data. The data was then analyzed to detect trends in the allocated task in the learning textbook and the tasks that inserted religious aspects. Result of the codification of tasks, there were 332 tasks most of which converged in the first three levels, which are LOTs and MOTs. In addition, from religious aspects, the tasks were mostly distributed at moral and sharia. However, no single task has been allocated for faith and worship. The result of the study can act as guidance to government, stakeholders, and textbook developers who are eager to modify their task allocated in such a way as to achieve higher level and to be aware of religious aspects to face their real life so that students can make use their cognitive skill and religious side in harmony.